The mutagenicity potential of holothurin of some Philippine holothurians - Pocsidio, Glorina N. (1983)
Holothurin in the form of ethanolic extract from the body walls of Actinopygalecanora Jaeger, Holothuria pulla Selenka and Holothuria fuscocinerea Jaeger was investigated for its mutagenicity potential. With the rec-assay on the Bacillus subtilisMarburg H17 (Rec) and M45 (Rec) strains, holothurin did not have direct DNA-damaging capacity, The Ames' test on Salmonella typhinuriumn strains TA1535 andTA1537 also demonstrated the infectivity of holothurin as a point mutagen before metabolic activation. However, holothurin was found highly mutagenic and clastogenicin vivo with the micronucleus test in the Swiss albino inice producing marked dose-related aberration scores as high as 62° / oo at 100 mg/kg H. fuscocinerea, 60°/00 at 200mg/kg H. pulla, and 51°/00 at 200 mg/kg A. lecanora administered intraperitoneally. Mutagenicity and clastogenicity of holothurin was reduced about 35-fold when administered orally. Toxic doses of holothurin adıninistered intraperitoneally to Swiss albino mice were at the minimal amounts of 200 mg/kg H. fu scocinerea and 700 mg/kgH. pulla.